2013
DOI: 10.1021/cb400308u
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Design of PDZ Ligands as Inhibitors of 5-HT2AReceptor/PSD-95 PDZ1 Domain Interaction Possessing Anti-hyperalgesic Activity

Abstract: Disrupting the interaction between the PDZ protein PSD-95 and the C-terminal domain of the 5-HT2A serotonin receptor has been shown to reduce hyperalgesia in a rodent model of neuropathic pain. Here, we designed and synthesized PDZ ligands capable of binding to the first PDZ domain (PDZ1) of the PSD-95 protein and evaluated their biological activity in vitro and in vivo. A series of substituted indoles was identified by docking simulations, and six novel analogues were synthesized. Three analogues displayed st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 33 publications
0
11
0
Order By: Relevance
“…6b-c ), none of which appear to be from residues Asp62, Leu107, Phe111 and Arg121, which are residues proposed to bind or to be affected by ligand-binding 24 25 . Typically, chemical shift perturbations of >0.1 ppm and up to 0.3 ppm are observed on binding even very weak ligands with K d ~ 300–500 μM 37 . Here, the maximum shift changes observed were less than 0.05 and are, therefore, considered non-specific.…”
Section: Resultsmentioning
confidence: 99%
“…6b-c ), none of which appear to be from residues Asp62, Leu107, Phe111 and Arg121, which are residues proposed to bind or to be affected by ligand-binding 24 25 . Typically, chemical shift perturbations of >0.1 ppm and up to 0.3 ppm are observed on binding even very weak ligands with K d ~ 300–500 μM 37 . Here, the maximum shift changes observed were less than 0.05 and are, therefore, considered non-specific.…”
Section: Resultsmentioning
confidence: 99%
“…One particular analogue (8b) was effective at suppressing the mechanical hyperalgesia in a rat model of neuropathic pain (Fig. 7A.3) (Boucherle et al, 2011;Vogrig et al, 2013).…”
Section: Pdz Domain Inhibitors In Neuronal Disordersmentioning
confidence: 99%
“…15 To compare the triazole compounds with current leading small-molecule PSD-95 PDZ inhibitors we synthesized Indole 1 and 2 ( Fig. 1C) according to literature 24 and tested them in the FP assay. Among 9-18, compound 10 showed robust inhibition of the PDZ2/probe interaction with a K i of 289 μM (Fig.…”
Section: Biological Evaluationmentioning
confidence: 99%
“…On the other hand, 10 is several fold more potent than Indole 1 and about 2-fold more potent than Indole 2. Vogrig et al 24 demonstrated that Indole 1 inhibits the PSD-95-PDZ1/ 5-HT 2A interaction with an IC 50 of 190 μM in an in vitro pulldown assay. Indole 2 was not tested in this assay, as it was estimated to be a weak binder based on 1 H-15 N HSQC NMR.…”
Section: Biological Evaluationmentioning
confidence: 99%
See 1 more Smart Citation